Myeloproliferative neoplasms and clonal haematopoiesis in patients with giant cell arteritis: a case–control and exploratory study. (9th April 2021) - Papo, Matthias; Friedrich, Chloé; Delaval, Laure; Boysson, Hubert de; Viallard, Jean-François; Bachmeyer, Claude; Sené, Thomas; Humbert, Sébastien; Duffau, Pierre; Contis, Anne; Agard, Christian; Gombert, Bruno; et al.
Abstract: Objectives: GCA is a large vessel vasculitis for which triggering factors remain unknown. Clonal haematopoiesis (CH) was associated with atherosclerosis through the induction of inflammation in myeloid cells, and data suggest that CH expansion and inflammation may support each other to induce a pro-inflammatory loop. Our objective was to describe the impact of JAK2 p.V617F -mutated myeloproliferative neoplasms (MPNs) on GCA and to screen MPN-free patients for CH mutations. Methods: We performed a retrospective case–control study comparing the characteristics of 21 GCA patients with MPN and 42 age- and gender-matched GCA patients without MPN. Also, 18 GCA patients were screened for CH through next-generation sequencing (NGS). Results: The most frequent associated MPN was essential thrombocythaemia (ET; n = 11). Compared with controls, GCA patients with MPN had less-frequent cephalic symptoms (71.4 vs 97.6%; P = 0.004) and higher platelet counts at baseline [485 × 10 9 /l (interquartile range 346–586) vs 346 (296–418); P = 0.02]. There was no difference between groups for other clinical features. Overall survival was significantly shorter in patients with MPN compared with controls [hazard ratio 8.2 (95% CI 1.2, 56.6); P = 0.03]. Finally, screening for CH using NGS in 15 GCA patients without MPN revealed CH in 33%. Conclusion: GCA patients with MPN display higher platelet counts and shorter overall survival than controls. This association is not fortuitous, given the possible pathophysiological relationship between the two diseases. CH was found in one-third of GCA patients, which may be higher than the expected prevalence for a similar age, and should be confirmed in a larger cohort.